2012
DOI: 10.1590/s1413-86702012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical Chlamydia trachomatis infection in sexually active adolescents from Salvador, Brazil

Abstract: The incidence of sexually transmitted diseases among adolescents is increasing worldwide. Genital Chlamydia trachomatis infection is one of the most prevalent sexually transmitted diseases in young women, and undetected disease is highly associated with long-term complications in women. Our goal was to determine the prevalence of cervical Chlamydia trachomatis infection in a sexually active population of female adolescents from Salvador, Brazil, and to describe their socio-demographic, behavioral, and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Variable rates of infection prevalence have been found, depending on which populations were studied and which diagnostic methods were used. Though the tracking of C. trachomatis is not mandatory in Brazil, several studies of prevalence have been performed in different regions of the country, with rates that have varied from 6% to 31% [13,14]. In the Amazon region, these studies are scarcer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable rates of infection prevalence have been found, depending on which populations were studied and which diagnostic methods were used. Though the tracking of C. trachomatis is not mandatory in Brazil, several studies of prevalence have been performed in different regions of the country, with rates that have varied from 6% to 31% [13,14]. In the Amazon region, these studies are scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…However, isolated studies carried out in this country have shown infection rates ranging from 6% to 31% among women [13,14]. The large range of reported rates reflects discrepancies in both methods used and populations evaluated [15].…”
Section: Introductionmentioning
confidence: 98%
“…Brazilian studies report a prevalence of C. trachomatis infection between 6.4 and 10.7% in women receiving routine gynecological exams, 6,1518 6.9 and 13.5% in women attending a family planning clinic, 13,19,20 15.6 and 20.7% in women attending an STI clinic, 20,21 9.4 and 11.1% in pregnant women, 20,22 and 14.5 and 31% in adolescents. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…En relación a estudios latinoamericanos, en una población de mujeres brasileras de un rango etario de 14 a 63 años (n: 121), utilizando muestras endo-cervicales, se demostró 20,79% de casos positivos mediante RPC convencional, destacando que 80% de los casos positivos perteneció a mujeres de 23 años o menos 11 . Otro estudio en Brasil, también con RPC convencional como sistema de detección, en una población femenina sexualmente activa de 10 a 19 años (n: 100), se determinó una prevalencia de infección de C. trachomatis en 31% de muestras endo-cervicales 12 . Por otro lado, en muestras endo-cervicales de 105 mujeres venezolanas (18 a 48 años), tanto sintomáticas como no sintomáticas, determinó una prevalencia de 10,4% de infección por C. trachomatis.…”
Section: Discussionunclassified